2008
DOI: 10.1136/thx.2008.098483
|View full text |Cite
|
Sign up to set email alerts
|

Using the lower limit of normal for the FEV1/FVC ratio reduces the misclassification of airway obstruction

Abstract: Aim: The prevalence of airway obstruction varies widely with the definition used. Objectives: To study differences in the prevalence of airway obstruction when applying four international guidelines to three population samples using four regression equations. Methods: We collected predicted values for forced expiratory volume in 1 s/forced vital capacity (FEV 1 /FVC) and its lower limit of normal (LLN) from the literature. FEV 1 /FVC from 40 646 adults (including 13 136 asymptomatic never smokers) aged 17-90+y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
410
1
6

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 485 publications
(433 citation statements)
references
References 61 publications
16
410
1
6
Order By: Relevance
“…As asthma is a disease of predominantly young people, the 0.70 criterion may, therefore, fail to diagnose many asthmatics as having obstruction, whereas in COPD, which is a disease of predominantly older people, the opposite is true; namely, too many may get the diagnosis of airflow obstruction without having it. FEV1/FVC declines with age [7], mainly due to an age-dependent loss of elastic fibres in the lungs, which reduces the elastic recoil of lung tissue. This is not per se a pathological process and so any consequent drop in FEV1/FVC cannot simply be ascribed to a disease such as COPD.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As asthma is a disease of predominantly young people, the 0.70 criterion may, therefore, fail to diagnose many asthmatics as having obstruction, whereas in COPD, which is a disease of predominantly older people, the opposite is true; namely, too many may get the diagnosis of airflow obstruction without having it. FEV1/FVC declines with age [7], mainly due to an age-dependent loss of elastic fibres in the lungs, which reduces the elastic recoil of lung tissue. This is not per se a pathological process and so any consequent drop in FEV1/FVC cannot simply be ascribed to a disease such as COPD.…”
mentioning
confidence: 99%
“…They reported ,20% misclassification in older age groups. SWANNEY et al [7] calculated false-positive test results as a percentage of all positive test results for airway obstruction in three large population-based samples of adults, including smokers and subjects with respiratory symptoms. They found that the LLN varied between prediction equations (57 equations available for males and 55 for females) and applying the GOLD fixed criterion of FEV1/FVC ,0.70 [4] caused false-positive rates of up to 60% when applied to entire populations.…”
mentioning
confidence: 99%
“…Este concepto ha sido ampliamente difundido [41][42][43][44] , generando controversia respecto de la definición de EPOC propuesta por GOLD, que sugiere su diagnóstico cuando la relación VEF 1 /CVF es inferior a 70%, sin importar la edad.…”
Section: Discussionunclassified
“…The nearest is the use of the European Coal and Steel Workers Population to provide percent predicted FEV 1 values; however, this population was standardised over 20 years ago and is based on a working white European population without ethnic minorities. [11][12][13] Similarly, younger people (age 30-40 years) with larger FVC values and greater respiratory reserve may already have sustained COPD-type damage to their lungs before they reach the <0.7 ratio threshold, so at this end of the age range there is a risk of under-diagnosis of COPD. 13 The debate regarding the diagnosis of COPD is more than just a debate over spirometry thresholds.…”
Section: Ps9mentioning
confidence: 99%
“…[11][12][13] Similarly, younger people (age 30-40 years) with larger FVC values and greater respiratory reserve may already have sustained COPD-type damage to their lungs before they reach the <0.7 ratio threshold, so at this end of the age range there is a risk of under-diagnosis of COPD. 13 The debate regarding the diagnosis of COPD is more than just a debate over spirometry thresholds. As many developing countries do not have access to spirometry or even to a reliable power supply, the usefulness of such diagnostic thresholds is limited.…”
Section: Ps9mentioning
confidence: 99%